Star-shaped and linear π-conjugated oligomers consisting of a tetrathienoanthracene core and multiple diketopyrrolopyrrole arms for organic solar cells - Komiyama, Hideaki; Adachi, Chihaya; Yasuda, Takuma (Beilstein Journal of Organic Chemistry, 2016)
Solution-processable star-shaped and linear π-conjugated oligomers consisting of an electron-donating tetrathienoanthracene (TTA) core and electron-accepting diketopyrrolopyrrole (DPP) arms, namely, TTA-DPP4 and TTA-DPP2, were designed and synthesized. Based on density functional theory calculations, the star-shaped TTA-DPP4 has a larger oscillator strength than the linear TTA-DPP2, and consequently, better photoabsorption property over a wide range of visible wavelengths. The photovoltaic properties of organic solar cells based on TTA-DPP4 and TTA-DPP2 with a fullerene derivative were evaluated by varying the thickness of the bulk heterojunction active layer. As a result of the enhanced visible absorption properties of the star-shaped π-conjugated structure, better photovoltaic performances were obtained with relatively thin active layers (40–60 nm).
Keywords: bulk heterojunction; diketopyrrolopyrrole; organic solar cells; star-shaped oligomers; tetrathienoanthracene